Culture and Gospel Some Observations from the Orthodox Tradition and Experience - Giannulatos, Anastasios G. (International review of mission, 1985)
The phenomenon of culture over the course of centuries presents an astonishing diversity; therefore it is difficult for “culture” to be confined by definitions. On the other hand, the gospel is often altered by various kinds of formulations or by existing expressions of Christianity. Therefore, prior to any study of the relations between culture and gospel, it will be useful to elucidate the extent of the meaning of these two terms.